THE IMPACT OF AI ON MARKETING: OPPORTUNITY OR THREAT? - Milena Fornazaric (Agora International Journal of Economical Sciences (AIJES), 2023)
Today we are talking about a new generation of AI, about generative AI, which came into mass use at the end of last year. Artificial intelligence is useful if we know how to use it and it has certainly been fundamentally changing the marketing universe for some time. In marketing, AI tools help in customer segmentation, in finding new customers who show propensity to buy, in product recommendations, in sales, in customer support, in the production of advertising messages, in the generation of responses on social networks, in purchasing behavior research, in algorithms for predicting buyer behavior, etc. ChatGPT and related technologies are the reality of individuals and organizations. New technologies develop very quickly and exponentially, where we do not know where and how the development will go, but we know that changes will happen. It is best to start preparing for the changes today. AI is not so much a technological change as it is a business change in organizations that requires change management, strategy and vision.
Keywords: 330